Tradisi Peminangan di Desa Sukosari, Jumantono, Wonogiri, dalam Perspektif Syariah - Suratno Suratno; Miftah Inayatul Af’ida (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Peminangan tradition in Sukosari Village, Jumantono, Wonogiri is a combination of the Shari'a that recommends sermons and the traditions that package them. This research aims to determine the marriage tradition in Sukosari Village, Jumantono District, Wonogiri Regency, Central Java and its conformity with sharia. This field research uses qualitative methods by collecting data through observation, supporting documents and interviews. The analysis obtained in this research is that this proposal tradition is unique to the local community, however, several things need to be taken into account regarding its suitability from a sharia perspective. Some recommendations for this tradition to comply with sharia are that the distance between the peminangan and marriage should not be too far, because there is an announcement of the proposal, if the marriage is canceled it will make the bride and groom very embarrassed. At the peminangan event, the positions of the guests watching the event should be arranged in such a way as to minimize ikhtilat. And a very important suggestion is that the process of exchanging rings, especially those worn by men, should be replaced with something other than gold and the handover should not be carried out directly by the bride and groom, to avoid touching the non mahrom. It is hoped that this research can provide constructive input for figures, leaders and the community of Sukosari, Jumantono, Wonogiri villages so that this unique tradition can be preserved by paying attention to its compatibility with sharia.